Undang-undang Pers Sebagai Lex Specialis - Lesmana, Tjipta (Pelita Harapan University, 2004)
Indonesia press enjoy optimal freedom following the down fall of Soeharto regime. The press now is free to criticize, even to condemn government officials, including the President. However, That freedom which is liberal in nature might results negative in impacts. People are conscious that too much freedom for the press could inflict disorder, or instability in society. The alternative to restrain liberal type of press freedom is by bringing the press to the court for its publicity. There has been more than 10 press law suits for the past 5 years. Mostly the press are weak in legal position. They criticize the Â judges for using penal code (KUHP) in trying the press. They urge the application Â of Press Law (Law No 40/1999), under the principle of